Study on Permeability and Blocking Resistance of Composite Specimen with Double-Layer Permeable Asphalt Mixture. (29th May 2019) - Tian, Xiaoge; Yuan, Huitong; Zhang, Ren; Xu, Yichao; Wang, Xiaofei
Abstract : In order to study the permeability and antiblocking performance of composite specimens with double-layer permeable asphalt mixture, three types of PAC-10 asphalt mixture with different target porosity (20%, 22%, and 24%) and PAC-16 asphalt mixture with a target porosity of 22% were designed, and the double-layer Marshall specimen was fabricated through "hot + hot" method. Their orthogonal vertical sections were scanned with X-ray CT. The pore distribution and its characteristics of the specimens were analyzed by digital image analysis technology. The permeability of composite specimens was studied through penetration test, and their blocking resistances were studied through using different particle sizes of fine machine-made sands as blocking materials. The results show that the permeable capacity increases linearly with the increase of porosity. The permeable capacity of PAC-16 with 22% porosity is greater than PAC-10 (20%, 22%, and 24%) porosity. The porosity of the upper layer increases, and the permeability of the double-layer composite samples increases linearly. The critical particle size causing blocking is 0.15 mm, followed by 0.3 mm. The vertical permeability coefficient decreases exponentially with the increasing of blocking times.